Favorable outcome in paraquat poisoning with acute kidney injury in a resource-limited setting: a case report - Ujjwal Kumar Shah; Achyoot Sharan Koirala; Kanchan Hathi; Parishrut Prasad Pandey; Kaschev Shrestha; Nabin Pahari; Jyotsna Joshi (Annals of Medicine & Surgery, 2026)
Introduction and importance: Paraquat poisoning remains a major public health challenge in Asia, with a mortality rate of 60%–80%, and acute kidney injury being a common complication. Case presentation: An 18-year-old female presented 6 hours after ingestion of approximately 5 mL of 24% (1.2 g) paraquat. Gastric lavage was performed within 30 minutes. She developed oral mucosal ulcers, dysphagia, and progressive AKI with serum creatinine rising from 1.0 mg/dL on the day of admission to 7.3 mg/dL by day 6 (eGFR declining from 83.7 mL/min/1.73m 2 to 7.7 mL/min/1.73 m 2 ). Chest radiography on day 3 showed prominent bronchovascular markings, and liver enzymes were significantly elevated. Despite indications for hemodialysis, it was not performed due to financial constraints. The patient was managed with intensive supportive care, including corticosteroids, N-acetylcysteine, antibiotics, proton pump inhibitors, and fluid resuscitation. Three-month follow-up showed no respiratory, gastrointestinal, or renal manifestations. Clinical discussion: Favorable prognostic factors included young age, rapid gastric decontamination, a moderate ingested dose (26 mg/kg), relatively preserved initial renal function, and early, aggressive supportive therapy. Conclusion: This case demonstrates that survival is possible in cases of moderate-dose paraquat poisoning with AKI, even without hemodialysis, when early supportive care is promptly initiated. While this single case cannot be generalized, it highlights the critical importance of rapid decontamination and aggressive supportive management in resource-limited settings where paraquat remains readily accessible, and it underscores the need for further research to develop affordable, evidence-based treatment protocols for paraquat poisoning in developing countries.